Nutritional properties of various oat and naked oat cultivars - Boeck Theresa; D’Amico Stefano; Zechner Elisabeth; Jaeger Henry; Schoenlechner Regine (Die Bodenkultur, 2018)
Two oat (Avena sativa L.) and ten naked oat (Avena nuda L.) cultivars grown on an experimental farm in two consecutive years were analyzed for their content of β-glucan, ash, fat, protein and Osborne protein fractions. Concentration of the antioxidant substances avenanthramides, tocopherols, tocotrienols and total phenolic compounds was analyzed. The antioxidant capacity of the oat cultivars was studied by ABTS•+-scavenging assay and FRAP assay. Cultivar Vazec and conservation cultivar Klimt showed high contents of fat, avenanthramides and total phenolic compounds, as well as a high antioxidant capacity. Klimt also had a high total protein content, and the highest proportion of avenanthramide 2c, which has the highest antioxidant activity of the analyzed avenanthramides. On the other hand, Klimt was also relatively low in β-glucan and tocopherols and tocotrienols. The two cultivars of husked oat, Effektiv and Max, have high yields and low prolamin contents, but showed poor results in all analyzed antioxidant parameters. Comparison of the two cultivation periods showed large differences in many of the analyzed parameters. The hot, dry climate of 2015 had negative influences on the nutritional quality of the oat, especially concerning the antioxidant properties. No cultivar could be identified that was robust against these climatic influences.